Control of Human PLP1 Expression Through Transcriptional Regulatory Elements and Alternatively Spliced Exons in Intron 1. (9th February 2015) - Hamdan, Hamdan; Kockara, Neriman T.; Jolly, Lee Ann; Haun, Shirley; Wight, Patricia A.
* These authors contributed equally to this work. Although the myelin proteolipid protein gene ( PLP1 ) encodes the most abundant protein in central nervous system (CNS) myelin, not much is known about the mechanisms that govern expression of the human gene ( hPLP1 ). Much more is known about the processes that regulate Plp1 gene expression in rodents. From studies with Plp1-lacZ transgenic mice, it was determined that the first intron of mouse Plp1 ( mPlp1 ) is required to attain high levels of expression in brain, concurrent with the active myelination period. Other studies have suggested that within mPlp1 intron 1 (>8 kb) lie several regions with enhancer-like activity. To test whether these sequences (and possibly others) in hPLP1 intron 1 are functional, deletion-transfection analysis was performed with hPLP1-lacZ constructs that contain various portions of the intron, or lack it altogether. Results presented here demonstrate the importance of hPLP1 intron 1 in achieving maximal levels of expression in the immortalized oligodendroglial cell line, Oli-neu. Deletion analysis indicates that the intron contains multiple positive regulatory elements which are active in Oli-neu cells. Some of these elements appear to be functionally conserved between human and mouse, while others are not. Furthermore, our studies demonstrate that multiple splice variants can be formed due to inclusion of extra (supplementary) exons from what is classically thought of as hPLP1 intron 1. Thus, splicing of these novel exons (which are not recognized as such in mPlp1 due to lack of conserved splice sites) must utilize factors common to both human and mouse since Oli-neu cells are of mouse origin.